Trends, geographical variation and factors associated with melatonin prescribing in general practices in England: A practice‐level analysis. Issue 5 (27th November 2021) - Wan, Mandy; Begum, Rukeya; Rashed, Asia N.
Abstract : An overview of melatonin prescribing trends and variation in England is described in this study. Prescription reimbursement data for melatonin in England were extracted from publicly available primary care datasets between 2008–2019. Melatonin prescribing rates, cost and product license status were described over time. Potential factors associated with melatonin prescribing were investigated using Poisson regression. Melatonin prescribing increased from 2.0 to 19.9 per 1000 people between 2008 and 2019. While prescriptions for licensed products increased from 6.5% to 88.2%, spending on unlicensed products was £10 million and accounted for 23.3% of the total prescription cost in 2019. Practices with a higher proportion of children and older people and those serving more deprived patient populations were associated with a higher rate of prescribing (rate ratio = 1.51, 1.66 and 1.59, respectively). Melatonin prescribing in England has increased exponentially over the last decade, with substantial spending on unlicensed products of unknown quality. Patient‐level analysis research is needed.